Formação de professores na contemporaneidade: desafios e possibilidades da parceria entre universidade e escola 1 2 3 4 - Souza, Samuel De [UNESP]; Borges, Cecilia; Ayoub, Eliana (UNICAMP - Faculdade de Educação, 2021)
This dossier addresses the issue of relations between the university and the school in the context of teacher education. Based on discussions about supervised internships, professional insertion at school, practice as a place of training and knowledge production, intergenerational partnerships and the relationship between initial training curriculum and school curriculum, the relations that have been established between the university and the school were problematized, with a view to the professionalization of teaching. For such purpose, we invited researchers from different countries, such as Brazil, Chile, Portugal and Belgium, whose articles present researches and experiences regarding partnerships articulating the university and the school, bringing contributions that dialogue with the themes announced above, in line with the specifics of each context. In conclusion, the six articles that make up the dossier provide possibilities for coping and successful experiences, besides a mapping of the relationship between university and school.

Este dossiê aborda a temática das relações entre a universidade e a escola no âmbito da formação de professores. A partir de discussões acerca dos estágios supervisionados, da inserção profissional na escola, da prática como lugar de formação e produção de saberes, das parcerias intergeracionais, bem como das relações entre currículo de formação inicial e currículo escolar, foram problematizadas as relações que vêm sendo estabelecidas entre a universidade e a escola, tendo em vista uma perspectiva de profissionalização do ensino. Para tal, reunimos pesquisadores(as) de diferentes países, como Brasil, Chile, Portugal e Bélgica, cujos artigos apresentam pesquisas e experiências a respeito de parcerias articulando a universidade e a escola, trazendo contribuições que dialogam com as temáticas antes anunciadas, em consonância com as especificidades de cada contexto. Concluindo, os seis artigos que compõem o dossiê aportam, além de um mapeamento da relação entre universidade e escola, possibilidades de enfrentamento e experiências exitosas.
Teacher education in contemporary times: challenges and possibilities of the partnership between university and school
Keywords: teacher education; professionalization of teaching; university-school partnership; supervised internship; formação de professores; profissionalização do ensino; parceria universidade-escola; estágio supervisionado